The Impact Of Intra And Inter-Firm Sourcing Strategy On Supplies' Quality, Delivery And Cost - Muhamad Jantan, Muhamad Jantan; T. Ramayah, T. Ramayah; Kbaw , Phaik Lean (Asian Academy of Management (AAM), 2000)
In recent years, the business environment has become extremely competitive. Firms, searching for sources of competitive advantage began to look into the potential of sourcing in adding value as purchased inputs account for 60% to 80% of cost of goods sold. Thus, the objective of this paper is to investigate which sourcing strategy, inter-firm or intra-firm, will lead to better supplies' quality, delivery and cost and whether in the process of achieving this outcome, it is moderated by environment-related factors. Intra-firm sourcing takes place when a firm procures materials, parts and components from within its corporate system, either a parent from its subsidiaries, or subsidiaries from their parent or from other related subsidiaries. By contrast, inter-fi rm sourcing occurs when a firm sources from independent, unrelated suppliers. The population for thi s study is the organizations that are involved in the manufacturing of electronics and electrical product located in Penang. The results reveal that in all of the three performance measures: quality, delivery and cost, intra-firm sourcing is seen to outperform inter-firm sourcing. Additionally, assets specificity is not a significant moderating variable on the differences in supplies' quality, delivery and cost of intra-firm and inter-firm sourcing, but bargaining power is. This study provides an avenue for further exploration on the potential of intra-firm sourcing.